Nature and growth of modern mathematics - Kramer, Edna E. (Paris Fawcett Premier Book, 1970)
Now available in a one-volume paperback, this book traces the development of the most important mathematical concepts, giving special attention to the lives and thoughts of such mathematical innovators as Pythagoras, Newton, Poincare, and Godel. Beginning with a Sumerian short story--ultimately linked to modern digital computers--the author clearly
Keywords: Mathematics; Mathematics history; Mathematics popular works